FENOMENA BIMBINGAN BELAJAR DI KALANGAN SISWA MADRASAH - Nurul Lailatul Aulia; Fitri Shofiatul Ulul Hikmah; Achmad Habibi; Rifqi Khairul Anam (As-Sulthan Journal of Education, 2026)
The increasing number of madrasah students participating in private tutoring (bimbel) is a response to the dynamics of academic competition and educational mobility, which have become increasingly competitive. This article aims to analyze various factors driving student participation through the lens of social reality construction using a literature review method. The results of the study indicate that students' decisions are influenced by a complex interaction between social and academic factors. Socially, participation is triggered by parental expectations that view private tutoring as a future investment, peer pressure that establishes "normal" effort standards, and the desire to achieve success symbols through public university entrance exams. Academically, the curricular gap between religious and general subjects, limited instructional time at madrasahs, and the advantages of practical methods and structured learning offered by tutoring institutions are primary drivers for students to seek enrichment outside of school. Thus, private tutoring functions as a strategic means to cope with social and academic pressures while simultaneously serving as an instrument to enhance the readiness of madrasah students for evaluations and further education.